1991
DOI: 10.1152/jn.1991.66.1.212
|View full text |Cite
|
Sign up to set email alerts
|

Neurogenic hyperalgesia: the search for the primary cutaneous afferent fibers that contribute to capsaicin-induced pain and hyperalgesia

Abstract: 1. A local cutaneous injury can produce primary hyperalgesia within the injured area and secondary hyperalgesia in the normal surrounding skin. An intradermal injection of capsaicin in humans causes intense pain and hyperalgesia to heat and to mechanical stimuli in the surrounding skin. Psychophysical studies in humans supported the conclusions that the hyperalgesia was predominantly the secondary type and depended on one set of neurons sensitizing another ("neurogenic hyperalgesia") and that the latter set of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
213
2
4

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 413 publications
(234 citation statements)
references
References 0 publications
14
213
2
4
Order By: Relevance
“…It is well known that nociceptors that are activated by capsaicin can become sensitized (Baumann et al 1991;Green 1989). To determine whether I A currents may contribute to this behavior, we have investigated how capsaicin modulates I A currents in TG neurons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is well known that nociceptors that are activated by capsaicin can become sensitized (Baumann et al 1991;Green 1989). To determine whether I A currents may contribute to this behavior, we have investigated how capsaicin modulates I A currents in TG neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on its concentration, length of application, and interstimulus interval, it can produce sensitization, hyperalgesia, or desensitization (Baumann et al 1991;Dessirier et al 2000;Green 1989). Capsaicin's activation of nociceptors arises from the depolarization produced by the opening of vanilloid receptors (whose K 1/2 approximately 1 M at physiological pH).…”
Section: Physiological Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microneurography studies in the peroneal nerve of man have shown that 6% of C fibre afferents are heat nociceptor units (Schmidt, Schmelz, Forster, Ringkamp, Torebj ork & Handwerker, 1995). In monkey hairy skin it is reported that heat nociceptor afferents make up 7% of C fibres (Baumann, Simone, Shain & LaMotte, 1991), and in monkey glabrous skin they make up 5·5% of nociceptive C fibres (Georgopoulos, 1976). It will be of interest to see the relative roles that the heat and polymodal nociceptor units play in generating neurogenic inflammation in primate skin.…”
Section: Species Differencesmentioning
confidence: 99%
“…Baumann reported that cutaneous application of capsaicin induced hyper-responses in unmyelinated small nerve fibers as well as axonal reflex-related neurogenic hyperalgesia. In addition to this peripheral process, alteration of primary afferents induces sensitization of second order spino-thalamic tract (STT) neurons, a major noxious pain pathway, known to have an influence on pain perception 5) . Sluka et al reported that, STT neurons demonstrated an increased background activity and increased response to innocuous stimuli for approximately 20 minutes following capsaicin injection 6) .…”
Section: Introductionmentioning
confidence: 99%